I A - topar elementlerin oqıtıwda klaster metodınan paydalanıw (SCIENCE and SOCIETY, 2025)
The article discusses the use of the Cluster method in teaching elements of group I A in chemistry les- sons. In class activities, this method is considered as a set of ideas expressed by students and increases students’ creativity